Organizational justice and employee in-role performance nexus: a dual theory perspective - Shabir Hyder; Muhammad Imran Malik; Saddam Hussain; Memoona Tasneem; Muhammad Kaleem; Adeel Saqib (Cogent Business & Management, 2022)
The organizational sustainability heavily depends upon employee performance. The aim of the study is to examine the relationship of organizational justice and in-role employee performance. Moreover, the organizational embeddedness and employee advocacy are used as mediator and moderator, respectively. A sample of 402 medical doctors was selected from different hospitals using snow-ball sampling technique. Their responses were gathered through a closed-ended questionnaire. The data collected were analyzed using partial-least square method. The study shows that organizational justice in the organization increases the employees performance. Organizational embeddedness mediates their relation, whereas advocating the needs of the employees moderates their relation. We have contributed to the existing theoretical model proposed in earlier literature by comprehensively analyzing the organizational justice impact on the in-role performance, i.e. by including the interactional justice impact as well. Furthermore, we also propose to include the role of employees' advocacy in enhancing the in-role performance of the employees. The hospital managers can enhance employees' in-role performance by treating them fairly; apply same rules without any bias, while developing open communication with them. These measures can be further improved by providing support. The cross-sectional nature of the study may restrict the generalizability of results.
Keywords: 650; conservation of resources theory; distributive justice; employee advocacy; employee embeddedness; interactional justice; Organizational justice; procedural justice; social exchange theory